3D Ultrasound-Guided Photoacoustic Imaging to Monitor the Effects of Suboptimal Tyrosine Kinase Inhibitor Therapy in Pancreatic Tumors - Claus, Abigail; Sweeney, Allison; Sankepalle, Deeksha M.; Li, Brian; Wong, Daniel; Xavierselvan, Marvin; Mallidi, Srivalleesha (Frontiers in Oncology, 2022)
Pancreatic cancer is a disease with an incredibly poor survival rate. As only about 20% of patients are eligible for surgical resection, neoadjuvant treatments that can relieve symptoms and shrink tumors for surgical resection become critical. Many forms of treatments rely on increased vulnerability of cancerous cells, but tumors or regions within tumors that may be hypoxic could be drug resistant. Particularly for neoadjuvant therapies such as the tyrosine kinase inhibitors utilized to shrink tumors, it is critical to monitor changes in vascular function and hypoxia to predict treatment efficacy. Current clinical imaging modalities used to obtain structural and functional information regarding hypoxia or oxygen saturation (StO2) do not provide sufficient depth penetration and require the use of exogenous contrast agents. Recently, ultrasound guided photoacoustic imaging (US-PAI) has garnered significant popularity as it can non-invasively provide multi-parametric information on tumor vasculature and function without the need for contrast agents. Here we built upon existing literature on US-PAI and demonstrate the importance of changes in StO2 values to predict treatment response, particularly tumor growth rate when the outcomes are sub-optimal. Specifically, we image xenograft mouse models of pancreatic adenocarcinoma treated with sub-optimal doses of a tyrosine kinase inhibitor cabozantinib. We utilize the US-PAI data to develop a multi-variate regression model that demonstrates therapy induced reduction in tumor growth rate can be predicted with 100% positive predictive power and a moderate (58.33%) negative predictive power when a combination of pre-treatment tumor volume, changes in StO2 values immediately pre-treatment and immediately post treatment were employed. Overall, our study indicates that US-PAI has the potential to provide label free surrogate imaging biomarkers that can predict tumor growth rate in suboptimal therapy.